2008
DOI: 10.3748/wjg.14.421
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of integrin β3 mRNA and vascular endothelial growth factor protein expression profiles with the clinicopathological features and prognosis of gastric carcinoma

Abstract: peritoneal metastasis, the mean MVD were significantly higher than those in patients of expanding type (P < 0.01), stage T1-T2 (P < 0.01), non-vessel invasion (P < 0.01), without lymphatic metastasis (P < 0.01), without hepatic and peritoneal metastasis (P < 0.01), respectively. It was found that the positive expression rate of integrin β3 mRNA was positively related to that of VEGF protein (P < 0.01) and MVD (P < 0.05), meanwhile the positive expression rate of VEGF protein was positively related to MVD (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…6). As seen in our study, the strong correlation of 18 F-FLT and Ki67 findings have been previously reported as prognostic indicators for malignant brain tumors (45).…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…6). As seen in our study, the strong correlation of 18 F-FLT and Ki67 findings have been previously reported as prognostic indicators for malignant brain tumors (45).…”
Section: Discussionsupporting
confidence: 68%
“…Treatment animals showed a statistically significant reduction in 18 F-FLT signal intensity, indicating decreased cellular proliferation and tumor expansion (Figs. 4A and 5A).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations